(untitled) (Revista científica Olimpia, 2024)
Chess is an important sport that begins to be practiced from an early age. The objective of this work is to characterize the psychological and psychosocial aspects that manifest in school chess players from the perception of chess coaches. This study is exploratory-descriptive. A survey was used for 24 coaches who attended the Chess improvement course for coaches at the “ISLA” Chess Study Center, of the Manuel Fajardo University of Physical Culture Sciences, in Havana, which allowed the collection of data. The results showed that among the positive psychosocial aspects, the most frequent was related to support and relationship with parents. For its part, in the negative psychosocial aspects, the most relevant was the lack of support and poor relationship with parents. These aspects must be taken into account by specialists when planning preparation and psychological control in training and competition.